Effect Of Nutritional Status On The Surgical Patients Using Subjective Global Assessment - Malik, Tahir Ali Mabroor; Akhtar, Fahad; Farrukh, Kanza; Arslan, Muhammad; Sakhizada, Fahim; Waqar, S.H. (Journal of Rawalpindi Medical College, 2025)
Objective: To assess the effects of nutritional status on surgical patients using a Subjective Global Assessment (SGA) scale Methods: This cross-sectional study was conducted in the Department of General Surgery, PIMS Islamabad from March 2022 to February 2024. All admitted patients in the ward were recruited by convenient sampling during the study period. All demographic data and clinical histories were recorded including SGA category, gender, age, surgical site infection, length of hospital stay and death. SPSS version 23 was used for statistical analysis. Descriptive statistics like mean with standard deviation (SD) and frequency (percentages) were used to analyze the collected data. Inferential statistics were also used for the comparison of study variables according to the SGA category. Results: A total of 1227 patients were included. The mean age of the patients was 41.98±16.82 years, with 744(60.6%) males and 483(39.4%) females. SGA ratings showed that 892(72.2%) patients fell in category A (well nourished), 333(27.1%) in B (mild/moderately malnourished), and 02(0.2%) in C (severely malnourished). The impact of SGA rating on gender distribution and management was non-significant as p-values were p=0.141 and p=0.158 respectively. The areas where significant impact (p<0.05) was seen were surgical site infection, deaths, age and length of hospital stay. An increased number of surgical site infections, longer hospital stays and more deaths were observed in mild/moderately or severely malnourished patients as compared to well-nourished patients. Conclusion: Malnourished patients have longer duration of hospitalization and those who have undergone surgery have higher wound infection rates. Keywords: Nutritional status, Surgical Site Infection, Hospital Stay.